Perilaku Komunikasi Petani Cabai Merah di Lahan Pasir Pantai Kecamatan Panjatan, Kabupaten Kulon Progo - Rizki Andriyani; Dwiningtyas Padmaningrum; Arip Wijianto; Hanifah Ihsaniyati (AGRITEXTS: Journal of Agricultural Extension, 2021)
Communication behavior shows the initiative of individuals or communities in adopting related innovations in seeking or disseminating information.This study aims to analyze: (1) attitudes, (2) subjective norms, (3) intentions, (4) communication behavior of farmers regarding the adoption of red chili cultivation in coastal sandy land, (5) the influence of attitudes on intentions, (6) the effect of subjective norm on intention, (7) influence of attitude on communication behavior, (8) influence of farmer's subjective norm on communication behavior, (9) influence of intention on communication behavior, (10) influence of attitude on communication behavior through intention, (11) influence of norm farmer's subjective perception of communication behavior through farmer's intention to adopt red chili in coastal sandy land. The basic research method is quantitative with survey techniques. The research locations were deliberately determined to include: Bugel Village, Pleret Village and Garongan Village, Panjatan District. Sampling using proportional random sampling technique consisted of 100 farmer respondents. Data analysis used path test (path analysis) with SPSS Statistics 22.0 program. The results showed that: (1) attitudes were included in the confident category, (2) subjective norms were included in the caring category, (3) intentions had a high category regarding communication behavior (4) communication behavior had a low category, (5) attitudes had no effect on communication behavior. intention, (6) farmer's subjective norm has no effect on intention, (7) farmer's attitude has no effect on communication behavior, (8) farmer's subjective norm has no effect on communication behavior, (9) farmer's intention has no effect on communication behavior, (10) farmer's attitude has no effect on communication behavior through farmers' intentions, (11) Farmers' subjective norms affect communication behavior through farmers' intentions to adopt red chilies on coastal sandy fields. The suggestion proposed is that there is a need to increase the intensity of gathering in farmer group activities and frequent discussion forums among red chili farmers in coastal sandy areas.